Protecting assets and enhancing welfare: The gender-differentiated potential of group-based approaches in Bangladesh - Rakib, Muntaha; Matz, Julia Anna (International Food Policy Research Institute, 2015)
Group-based approaches have received a lot of attention in the recent past due to their possible role in securing household welfare in the presence of adverse events. Using detailed household survey data from Bangladesh, the present paper tests this potential by first examining the factors associated with men’s and women’s participation in different types of groups. Subsequently, we investigate the relationship between social and political capital and welfare among agricultural households in the presence of shocks, addressing the inherent endogeneity with the help of instrumental variables estimation and allowing for differences by gender, both in group membership and in asset ownership. The data suggest that household heads and their spouses are members of different groups overall: while the former mainly participate in farmer groups, the latter are mainly active in credit groups. Furthermore, there is evidence for a positive association of social and political capital with household-level welfare, mainly driven by social capital and particularly with consumption expenditure of the household and asset holdings of the household head. Interestingly, our results suggest that this effect is not driven by the mere participation in groups, but also by other aspects of social capital such as informal networks, of both household heads and their spouses.